2020
DOI: 10.5194/nhess-20-1513-2020
|View full text |Cite
|
Sign up to set email alerts
|

A methodology to conduct wind damage field surveys for high-impact weather events of convective origin

Abstract: Abstract. Post-event damage assessments are of paramount importance to document the effects of high-impact weather-related events such as floods or strong wind events. Moreover, evaluating the damage and characterizing its extent and intensity can be essential for further analysis such as completing a diagnostic meteorological case study. This paper presents a methodology to perform field surveys of damage caused by strong winds of convective origin (i.e. tornado, downburst and straight-line winds). It is base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The moister and relatively warm marine boundary layer of that area increases low‐tropospheric instability and makes environmental conditions more favourable to deep convection (Miglietta et al ., 2017), which is also consistent with the spatial and temporal distribution of lightning events (Taszarek et al ., 2019). This has been highlighted by the exhaustive monitoring of tornadoes and waterspouts in Catalonia and the Balearic Islands during the last three decades by several studies (Gayà et al ., 2001; Gayà, 2011; Arús, 2018; Rodríguez et al ., 2020). This may explain the higher detection of non‐damaging or weakly‐damaging events such as waterspouts and (E)F0 tornadoes in this subarea, in contrast to the rest of the Iberian Peninsula where the ratio of these types of events is much lower.…”
Section: Methodsmentioning
confidence: 99%
“…The moister and relatively warm marine boundary layer of that area increases low‐tropospheric instability and makes environmental conditions more favourable to deep convection (Miglietta et al ., 2017), which is also consistent with the spatial and temporal distribution of lightning events (Taszarek et al ., 2019). This has been highlighted by the exhaustive monitoring of tornadoes and waterspouts in Catalonia and the Balearic Islands during the last three decades by several studies (Gayà et al ., 2001; Gayà, 2011; Arús, 2018; Rodríguez et al ., 2020). This may explain the higher detection of non‐damaging or weakly‐damaging events such as waterspouts and (E)F0 tornadoes in this subarea, in contrast to the rest of the Iberian Peninsula where the ratio of these types of events is much lower.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the authors in [35] found that the yearly average economical losses produced only by hail events in the western area of Catalonia were EUR 15M for the period 2000-2009. In the case of straight-line winds or tornadoes, the frequency of occurrence is lower, although most of the events affect densely populated areas and therefore, the economic impact may be even higher [36,37].…”
Section: Motivationmentioning
confidence: 99%
“…This can be seen in Figure 4, which shows the track of the convective cell that produced the tornado, overlaid on top of the topography. Due to the resolution and the scanning strategies, it has never been possible to observe the tornado itself with the XRAD (smaller than 1 km wide), and thus, as in analyzed cases from the past, the tornado information was obtained with "on the ground" post-event debris analysis [37]. Additionally, in this case, the storm propagated up the valley (valley floor height of 250 m ASL), and the closest radar, CDV, was located 42 km away at 825 m ASL.…”
Section: Samurai Performancementioning
confidence: 99%
“…Most of the tornadoes passed outside of settlements and were found only with the use of satellite images of forest damage tracks. Ideally, forest damage survey or high-resolution aerial imagery of damaged forest is needed to correctly estimate the intensity of such tornadoes [13,15,65,66]. Due to their lack, we used high-resolution (with~0.5 m pixel size) satellite images from Google Earth to assess tornado intensity.…”
Section: Tornado Tracks Identification and Characteristics Estimatementioning
confidence: 99%